Revitalisasi Identitas Digital TK Pelita Insan Untuk Meningkatkan Visibilitas Dan Kredibilitas Sekolah - Ananto Tri Sasongko; Wiyanto; Agung Nugroho; Sufajar Butsianto (RECORD: Journal of Loyality and Community Development, 2024)
The abstract The revitalization of Pelita Insan Kindergarten's digital identity aimed to enhance the school's visibility and credibility by utilizing the .sch.id domain, the official domain for educational institutions in Indonesia. This domain provides an authoritative and trusted identity, which bolsters public confidence in the school. The school's website, using this domain, serves as an effective medium for disseminating information, facilitating communication with parents, and reinforcing the institution's image. The process included domain registration, content management, and the development of digital communication strategies to establish a professional online presence. This community service initiative demonstrated that leveraging the .sch.id domain significantly enhances the school's branding and digital footprint, making information more accessible to the broader community. This effort not only strengthens the school's online identity but also fosters greater engagement and transparency, ultimately supporting the educational mission of Pelita Insan Kindergarten. By improving digital access, the school can better serve its community, providing essential updates and resources in a timely and efficient manner.